Export from Seagrass Meadows Contributes to Marine Carbon Sequestration - Duarte, Carlos M.; Krause-Jensen, Dorte (Frontiers in Marine Science, 2017)
Seagrasses export a substantial portion of their primary production, both in particulate and dissolved organic form, but the fate of this export production remains unaccounted for in terms of seagrass carbon sequestration. Here we review available evidence on the fate of seagrass carbon export to conclude that this represents a significant contribution to carbon sequestration, both in sediments outside seagrass meadows and in the deep sea. The evidence presented implies that the contribution of seagrass meadows to carbon sequestration has been underestimated by only including carbon burial within seagrass sediments.